Genetics and Molecular Biology: With Fundamentals of Biostatistics (Tata McGraw-Hill Education Pvt. Ltd., 2010)
Hyde’s Genetics and Molecular Biology teaches the principles of genetics with an innovative approach that emphasizes the basic concepts involved in solving problems as well as teaching students how to manipulate genetic data. This text maintains the rigor that faculty require in a genetics book, while incorporating a student friendly presentation style that helps the reader grasp the subject in easiest manner. Exhaustive Coverage to all important topics such as Chromosomes and Cell Cycles, Mendelian and Non Mendelian Inheritance, Linkage, Mapping, Pedigree Analysis, Gene Expression, RDT, Mutations, Application of genetic principles to problems helps reader to directly compare the concept with the real life situations.